Is E-FAST possible and useful on the battlefield? A feasibility study during medical courses in hostile environment (MEDICHOS): preliminary results. Issue 5 (October 2019) - Renard, Aurélien; Martinet, C; Cungi, P J; Combes, E; Gasperini, G; Cazes, N; Carfantan, C; Faivre, A; Travers, S; Kelway, C; Benner, P
Abstract : Introduction: The extent of the French forces' territory in the Sahel band generates long medical evacuations. In case of many victims, to respect the golden hour rule, first-line sorting is essential. Through simulation situations, the aim of our study was to assess whether the use of ultrasound was useful to military doctors. Methods: In combat-like exercise conditions, we provided trainees with a pocket-size ultrasound. Every patient for whom the trainees chose to perform ultrasound in role 1 was included. An extended focused assessment with sonography for trauma (E-FAST) was performed with six basic sonographic views. We evaluated whether these reference views were obtained or not. Once obtained by the trainees, pathological views corresponding to the scenario were shown to assess whether the trainees modified their therapeutic management strategy and their priorities. Results: 168 patients were treated by 15 different trainee doctors. Of these 168 patients, ultrasound (E-FAST or point-of-care ultrasound) was performed on 44 (26%) of them. In 51% (n=20/39) of the situations, the practitioners considered that the realisation of ultrasound had a significant impact in terms of therapeutic and evacuation priorities. More specifically, it changed therapeutic decisions in 67% of time (n=26/39) and evacuation priorities in 72% of time (n=28/39). Conclusion: This original work showed that ultrasound on the battlefield was possible and useful. To confirm these results, ultrasound needs to be democratised and assessed in a real operational environment.